Full Employment and the Welfare State - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 1996)
What were the asserted complementarities between the welfare state and full-employment policies, and why do these complementarities look less convincing today?
Keywords: E24; J20; J21; 330; EMPLOYMENT; LABOUR MARKET; WELFARE STATE